Koi baat nahin - Atiya, Naqvi; Mahreen, Zuberi (book group Karachi, 2002)
"Koi Baat Nahin" is a common Urdu phrase that translates to "It's okay" or "No problem." It's often used to express understanding, reassurance, or to downplay a situation. It's a versatile phrase that can be used in various contexts, from casual conversations to more formal situations.